Mechanistic analysis of the sub chronic toxicity of La and Gd in Daphnia magna Based on TKTD modelling and synchrotron X-ray fluorescence imaging - Marion Leonie Revel and Kadda Medjoubi and Sandrine Charles and Andrew Hursthouse and Susanne Heise (Chemosphere, 2024)
The release of lanthanides (Ln) into the environment has increased in recent decades due to their expanding applications in society. Studying their toxicity in aquatic ecosystems is urgent and challenging, with contradictory evidence presented in the literature. This study compared the biodistribution of La and Gd in Daphnia magna exposed to sub-chronic conditions and developed the first Toxicokinetic-Toxicodynamic (TKTD) model for these lanthanides with this model crustacean. D. magna were initially exposed for 7 days to concentrations close to the LC50 of La (2.10 mg L-1) and Gd (1.70 mg L−1). After exposure, half of the live daphnids were introduced in a clean media to allow depuration over 24 h, while the other organisms were directly prepared for synchrotron imaging measurements. Synchrotron X-ray fluorescence analysis revealed that metal distribution in the organisms was similar for both La and Gd, predominantly localized in the intestinal tract, even after the depuration process. These results indicate that ingested metal can adversely affect organisms under sub-chronic exposure conditions, highlighting the importance of using nominal concentrations as a more suitable indicator of metal bioavailability for risk assessment. The General Unified Threshold Model of Survival (GUTS) TKTD framework, in its reduced form (GUTS-RED), was developed for La and Gd using dissolved and nominal concentrations. D. magna were exposed for 7 days to concentrations from 0.5 to 5 mg L−1 of La or Gd and mortality monitored daily. The mechanistic model revealed a faster toxicokinetics for La than Gd and a higher toxicity for Gd than La in the organism. This study confirmed, despite similar chemical properties, the variation in both toxicity and toxicokinetics between these two metals.
Keywords: Rare Earth Elements; emerging contaminants; Ecotoxicity; Impact on daphnids